Intraoperative electrochemotherapy of colorectal liver metastases. Issue 3 (30th April 2014) - Edhemovic, Ibrahim; Brecelj, Erik; Gasljevic, Gorana; Marolt Music, Maja; Gorjup, Vojka; Mali, Barbara; Jarm, Tomaz; Kos, Bor; Pavliha, Denis; Grcar Kuzmanov, Biljana; Cemazar, Maja; Snoj, Marko; et al.
<x xml:space="preserve">Abstract</x> Background and Objectives Electrochemotherapy is effective in treatment of various cutaneous tumors and could be translated into treatment of deep‐seated tumors. With this aim a prospective pilot study was conducted to evaluate feasibility, safety, and efficacy of intraoperative electrochemotherapy in the treatment of colorectal liver metastases. Methods Electrochemotherapy with bleomycin was performed during open surgery, by insertion of long needle electrodes into and around the tumor according to the individualized pretreatment plan. Results A 29 metastases in 16 patients were treated in 16 electrochemotherapy sessions. No immediate (intraoperative) and/or postoperative serious adverse events related to electrochemotherapy were observed. Radiological evaluation of all the treated metastases showed 85% complete responses and 15% partial responses. In a group of seven patients that underwent a second operation at 6–12 weeks after the first one, during which electrochemotherapy was performed, the histology of resected metastases treated by electrochemotherapy showed less viable tissue (P = 0.001) compared to non‐treated ones. Conclusions Electrochemotherapy of colorectal liver metastases proved to be feasible, safe, and efficient treatment modality, providing its specific place in difficult to treat metastases, located in the vicinity of major hepatic vessels, not amenable to surgery or radiofrequency ablation. J. Surg. Oncol. 2014 110:320–327. © 2014 Wiley Periodicals, Inc.